Investigating neural efficiency of elite karate athletes during a mental arithmetic task using EEG - DURU, ADİL DENİZ (SPRINGER, 2018)
Neural efficiency is proposed as one of the neural mechanisms underlying elite athletic performances. Previous sports studies examined neural efficiency using tasks that involve motor functions. In this study we investigate the extent of neural efficiency beyond motor tasks by using a mental subtraction task. A group of elite karate athletes are compared to a matched group of non-athletes. Electroencephalogram is used to measure cognitive dynamics during resting and increased mental workload periods. Mainly posterior alpha band power of the karate players was found to be higher than control subjects under both tasks. Moreover, event related synchronization/desynchronization has been computed to investigate the neural efficiency hypothesis among subjects. Finally, this study is the first study to examine neural efficiency related to a cognitive task, not a motor task, in elite karate players using ERD/ERS analysis. The results suggest that the effect of neural efficiency in the brain is global rather than local and thus might be contributing to the elite athletic performances. Also the results are in line with the neural efficiency hypothesis tested for motor performance studies.
Keywords: Elite athletes; Karate; EEG; Neural efficiency; Event related synchronization (ERS); Mental subtraction; HIGH-RESOLUTION EEG; WORKING-MEMORY; BRAIN; INTELLIGENCE; SPORTS; ERD